Hydrothermal Synthesis of Flake-Flower NiO and Its Gas Sensing Performance to CO - Qian, Guochao; Peng, Qingjun; Zou, Dexu; Wang, Shan; Yan, Bing (Frontiers in Materials, 2020)
In this work, flake-flower NiO was successfully prepared via a facile hydrothermal method. The microstructure of the synthesized sample was characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). We find that the hierarchical flake-flower structure was assembled by numerous nanosheets with different size and shape. The fabricated sensor based on the obtained microstructure exhibited excellent gas sensing performance including high response, outstanding selectivity and stability towards 5 ppm CO at the optimal working temperature of 250 °C. A plausible gas sensing mechanism was given out to explain how the nanosheet assembly morphology affects the gas sensing performance of the flake-flower structure.